Pendidikan Dokter Berbasis Kompetensi dan Moralitas dengan Metode Problem Based Learning pada FK UMY - Hidayati, Titiek (Universitas Muhammadiyah Yogyakarta, 2004)
To face the coming era, Islamic Revealed Knowledge is really important because of several reasons: (1). Muhammadiyah University has to produce graduates to fulfill the need of 21st century Indonesian Scholar with nation- ally/intemationally qualification; (2). The increase of Islamic society followed by high quality demand reveals the development of Muhammadiyah UniverÂ¬sity as center of human resources development; (3) Islam as the way of live should be apllied in daily activities, especially as a Muslim scholars graduÂ¬ated from Muhammadiyah University; (4). There is no clear definition and principles about Islamic medicine and/or other Islamic revealed knowledge in medical filed.